Glass for covering semiconductor element, material for covering semiconductor element, and sintered body for covering semiconductor element

By using SiO2-ZnO-Al2O3-type glass and containing Zn2SiO4 as the main crystal after heat treatment, the existing problems of environmental pollution, high thermal expansion coefficient and high surface charge density in the existing glass for covering semiconductor components are solved, and the application of low-quality glass is achieved Glass materials with low thermal expansion coefficient and low surface charge density of voltage-resistant semiconductor components.

CN119451920APending Publication Date: 2025-02-14NIPPON ELECTRIC GLASS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380050977.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-29
Filing Date
2023-06-16
Publication Date
2025-02-14

Smart Images

  • Figure BDA0005218230200000081
    Figure BDA0005218230200000081
Patent Text Reader

Abstract

Provided is a glass for covering a semiconductor element, said glass having a low environmental load, a low coefficient of thermal expansion, and a low surface charge density. This glass for covering a semiconductor element is characterized by containing, in mol%, 30% to less than 53% of SiO2, 15% to 30% of ZnO, 2% to 14% of Al2O3, 10% of B2O3, and more than 11% but 30% or less of MgO + CaO, as a glass composition, and by containing substantially no lead component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to glass for covering a semiconductor element, a material for covering a semiconductor element, and a sintered body for covering a semiconductor element. Background Art

[0002] Semiconductor elements such as silicon diodes and transistors are usually coated with glass on the surface including the PN junction of the semiconductor element, thereby stabilizing the surface of the semiconductor element and suppressing the degradation of characteristics over time.

[0003] The properties required of glass for covering semiconductor elements include: (1) a thermal expansion coefficient that is suitable for that of the semiconductor element so as to prevent cracks from being caused by a difference in thermal expansion coefficient with the semiconductor element; (2) the ability to cover at low temperatures (e.g., below 900°C) to prevent degradation of the properties of the semiconductor element; and (3) the absence of impurities such as alkali components that may adversely affect the surface of the semiconductor element.

[0004] Traditionally, zinc-based glasses such as ZnO-B2O3-SiO2 and lead-based glasses such as PbO-SiO2-Al2O3 and PbO-SiO2-Al2O3-B2O3 glasses have been known as glasses for covering semiconductor elements. However, from the perspective of operability, lead-based glasses such as PbO-SiO2-Al2O3 and PbO-SiO2-Al2O3-B2O3 glasses have become mainstream (for example, refer to Patent Documents 1 to 4).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 48-43275

[0008] Patent Document 2: Japanese Patent Application Publication No. 50-129181

[0009] Patent Document 3: Japanese Patent Publication No. 1-49653

[0010] Patent Document 4: Japanese Patent Application Publication No. 2008-162881 Summary of the invention

[0011] Technical problem that the invention aims to solve

[0012] However, the lead component of the lead-based glass is a component that is harmful to the environment. In addition, the zinc-based glass mentioned above cannot be said to be completely harmless to the environment because it contains a small amount of lead and bismuth components.

[0013] Furthermore, zinc-based glass tends to have a high coefficient of thermal expansion, and when the surface of a semiconductor element such as Si is covered with the glass, cracks or warping may occur in the semiconductor element.

[0014] On the other hand, if the content of SiO2 in the glass composition is increased, the thermal expansion coefficient is reduced, and the reverse voltage of the semiconductor element becomes higher, and the semiconductor element is less likely to fail. However, if the reverse voltage becomes higher, the reverse leakage current of the semiconductor element becomes larger. In particular, in semiconductor elements for low withstand voltage, the reverse leakage current becomes a problem, so it is necessary to suppress the reverse leakage current by reducing the surface charge density of the glass.

[0015] Therefore, the present invention has been made in view of the above circumstances, and a technical object thereof is to provide a glass for covering a semiconductor element which has a small environmental load, a low thermal expansion coefficient, and a low surface charge density.

[0016] Technical solutions to the problem

[0017] The inventors of the present invention have conducted intensive research and found that the above-mentioned technical problems can be solved by using SiO2-ZnO-Al2O3 glass having a specific glass composition, and thus proposed the present invention. That is, the glass for covering semiconductor elements of the present invention is characterized in that, as a glass composition, it contains, in mole %, SiO2 of 30% or more and less than 53%, ZnO of 15% to 30%, Al2O3 of 2% to 14%, B2O3 of 0 to 10%, MgO+CaO of more than 11% and less than 30%, and substantially no lead component. Here, "MgO+CaO" refers to the total amount of MgO and CaO. In addition, "substantially free of" means that the component is not intentionally added as a glass component, and does not mean that impurities that are inevitably mixed are completely excluded. Specifically, it means that the content of the component including impurities is less than 0.1% by mass.

[0018] As described above, the glass for covering semiconductor elements of the present invention limits the content range of each component. As a result, the environmental load is small, the thermal expansion coefficient is low, and the surface charge density is reduced. As a result, it can be suitable for covering semiconductor elements with low withstand voltage.

[0019] The glass for covering a semiconductor element of the present invention preferably contains Zn2SiO4 as a main crystal after heat treatment. Here, "heat treatment" means heat treatment at 800 to 1000°C for 10 minutes or more.

[0020] The semiconductor element covering material of the present invention preferably includes glass powder containing the above-mentioned semiconductor element covering glass.

[0021] The semiconductor element covering material of the present invention preferably has a thermal expansion coefficient of 20×10 -7 / ℃ and above 48×10 -7 / °C or less. This makes it easy to avoid cracks and warpage of the semiconductor element. Here, the "thermal expansion coefficient in the temperature range of 30°C to 300°C" refers to a value measured by a push rod type thermal expansion coefficient measuring device.

[0022] The semiconductor element covering sintered body of the present invention is characterized in that it contains Zn2SiO4 as a main crystal, and the volume ratio of Zn2SiO4 is 10% to 40%. In addition, the semiconductor element covering sintered body refers to a sintered body obtained by heat treating the semiconductor element covering material.

[0023] The sintered body for covering a semiconductor element of the present invention is characterized in that it contains Zn2SiO4 as a main crystal and has a porosity of 10% or less.

[0024] The sintered body for covering a semiconductor element of the present invention preferably contains, as a glass composition, in mol %, the following: SiO2 30% to less than 53%, ZnO 15% to 30%, Al2O3 2% to 14%, B2O3 0 to 10%, MgO+CaO greater than 11% and less than 30%, and substantially contains no lead component.

[0025] Effects of the Invention

[0026] According to the present invention, it is possible to provide a semiconductor element covering glass having a small environmental load, a low thermal expansion coefficient, and a low surface charge density. DETAILED DESCRIPTION

[0027] The glass for covering semiconductor elements of the present invention is characterized in that, as a glass composition, it contains, in mole %, SiO2 30% to less than 53%, ZnO 15% to 30%, Al2O3 2% to 14%, B2O3 0 to 10%, MgO+CaO greater than 11% and less than 30%, and substantially no lead component. The following is an explanation of the reasons for limiting the content of the crystalline phase and each component. It should be noted that in the following description of the content of each component, unless otherwise specified, % refers to mole %. In addition, unless otherwise specified, the numerical range represented by "to" in this specification refers to the range that includes the numerical values ​​recorded before and after "to" as the minimum and maximum values, respectively.

[0028] SiO2 is the component that forms the network of glass and is the component that improves acid resistance. Additionally, it is a constituent of Zn2SiO4. The content of SiO2 is 30% or more and less than 53%, preferably 30% - 52%, 30% - 51%, 30% - 50%, 30% or more and less than 50%, 32% - 48%, and particularly preferably 35% - 45%. If the content of SiO2 is too small, the coefficient of thermal expansion tends to increase easily, and additionally, the acid resistance decreases. Also, it is difficult to precipitate Zn2SiO4, and the coefficient of thermal expansion of the covering material becomes too high, resulting in a large warpage when firing the covering material (in Japanese: 焼成被覆). On the other hand, if the content of SiO2 is too large, the firing temperature becomes too high, and it is impossible to form the covering layer at an appropriate temperature.

[0029] ZnO is the component that stabilizes the glass. Additionally, it is a constituent of Zn2SiO4. The content of ZnO is 15% - 30%, preferably 17% - 28%, 19% - 26%, 19.5% or more and less than 25%, and particularly preferably 20% - 24%. When the content of ZnO is too small, the devitrification property during melting becomes strong, and it is difficult to obtain a homogeneous glass. Also, it is difficult to precipitate Zn2SiO4, and the coefficient of thermal expansion of the covering material becomes too high, resulting in a large warpage when firing the covering material. On the other hand, when the content of ZnO is too large, the acid resistance tends to decrease easily. Additionally, the crystallinity becomes too strong, the viscosity during firing increases sharply, and defects such as bubbles are likely to be included in the covering material.

[0030] SiO2 + ZnO (the total amount of SiO2 and ZnO) is preferably 45% - less than 80%, 50% - 70%, and particularly preferably 55% - less than 65%. If the total amount of SiO2 and ZnO is too small, it is difficult to precipitate Zn2SiO4, and the coefficient of thermal expansion of the covering material becomes too high, resulting in a large warpage when firing the covering material. On the other hand, if the total amount of SiO2 and ZnO is too large, the crystallinity becomes too strong, the viscosity during firing increases sharply, and defects such as bubbles are likely to be included in the covering material.

[0031] Al2O3 is the component that stabilizes the glass and adjusts the surface charge density. The content of Al2O3 is 2% - 14%, preferably 4% - 12%, and particularly preferably 5% - 10%. If the content of Al2O3 is too small, the glass is likely to devitrify during forming. On the other hand, if the content of Al2O3 is too large, the surface charge density may become too large.

[0032] B2O3 is the component that forms the network of glass and is the component that improves the softening fluidity. The content of B2O3 is 0 - 10%, preferably 0 - 7%, 0 - 5%, and particularly preferably 0 - 3%. If the content of B2O3 is too large, it is difficult to crystallize the glass, and there is also a tendency for the acid resistance to decrease.

[0033] MgO and CaO are components that reduce the viscosity of glass. The total amount of MgO and CaO is greater than 11% and less than 30%, preferably 12% to 28%, 15% to 25%, and particularly preferably 16% to 24%. When the total amount of MgO and CaO is too small, the firing temperature of the glass tends to rise. On the other hand, when the total amount of MgO and CaO is too large, the thermal expansion coefficient may become too high, the chemical resistance may decrease, and the insulation may decrease.

[0034] From an environmental point of view, it is preferred that lead components (such as PbO, etc.) are substantially not contained, and Bi2O3, F, and Cl are substantially not contained. In addition, it is preferred that alkali components (Li2O, Na2O, and K2O) that have an adverse effect on the surface of semiconductor elements are substantially not contained.

[0035] In addition to the above-mentioned components, other components (such as SrO, BaO, MnO2, Nb2O5, Ta2O5, CeO2, Sb2O3, etc.) may be contained up to 7% (preferably up to 3%).

[0036] The glass for covering semiconductor elements of the present invention preferably contains Zn2SiO4 as the main crystal after heat treatment. Zn2SiO4 has a thermal expansion coefficient very close to that of silicon, which is the object of covering the glass of the present invention, and has the effect of greatly suppressing the warping during firing after covering. In addition, in addition to Zn2SiO4, crystals such as ZnAl2O4 may also be contained at the same time.

[0037] In addition, the volume ratio of Zn2SiO4 is preferably 10% to 40%, 12% to 35%, and particularly preferably 15% to 30%. If the volume ratio of Zn2SiO4 is too small, the thermal expansion coefficient of the covering material becomes too high, and the warping during firing after covering becomes larger. On the other hand, if the volume ratio of Zn2SiO4 is too large, the viscosity of the glass increases sharply above the softening point, and it is easy to contain defects such as bubbles. The "volume ratio of Zn2SiO4" refers to the value obtained by removing the background of the peak of Zn2SiO4 obtained by X-ray diffraction, dividing the integrated intensity of the sharp peak of the crystalline phase by the integrated intensity of the broad peak of the amorphous layer (glass), and then multiplying it by one hundred.

[0038] The semiconductor element covering material of the present invention preferably comprises a material obtained by processing the above-mentioned semiconductor element covering glass into a powdered state, i.e., glass powder. If processed into glass powder, the surface of the semiconductor element can be easily covered by, for example, a paste method, an electrophoretic coating method, etc. Then, by heat-treating the semiconductor element covering material, the surface of the semiconductor element can be covered with a semiconductor element covering sintered body.

[0039] Average particle size of glass powder D 50It is preferably 25 μm or less, and particularly preferably 15 μm or less. 50 If the average particle size D of the glass powder is too large, it will be difficult to gelatinize. In addition, it will be difficult to attach the powder by electrophoresis. 50 The lower limit of is not particularly limited, but is in practice 0.1 μm or more. 50 " is a value measured on a volume basis, and refers to a value measured by a laser diffraction method.

[0040] The glass powder can be obtained, for example, by mixing raw material powders of the respective oxide components into a batch, melting the batch at about 1500° C. for about 1 hour to vitrify the batch, and then molding the batch (and then pulverizing and classifying the batch as necessary).

[0041] In the semiconductor element covering material of the present invention, after heat treatment, the thermal expansion coefficient in the temperature range of 30°C to 300°C is preferably 20×10 -7 / ℃ or above, 48×10 -7 / ℃ or less, particularly preferably 30×10 -7 / ℃ or above, 45×10 -7 If the thermal expansion coefficient is outside the above range, cracks, warping, etc. are likely to occur due to the difference in thermal expansion coefficient with the semiconductor element.

[0042] In the semiconductor element covering material of the present invention, after heat treatment, the surface charge density is preferably 10×10 11 / cm 2 Below, particularly preferably 8×10 11 / cm 2 If the surface charge density is too high, the withstand voltage will be improved, but at the same time, the leakage current will tend to be increased. It should be noted that the "surface charge density" refers to a value measured by the method described in the Examples section described later.

[0043] The sintered body for covering a semiconductor element of the present invention contains Zn2SiO4 as the main crystal. In addition, preferably, as a glass composition, it contains, in mole %, SiO2 30% to less than 53%, ZnO 15% to 30%, Al2O3 2% to 14%, B2O3 0 to 10%, MgO+CaO greater than 11% and less than 30%, and substantially contains no lead component. In addition, the preferred range of the content of each component of the sintered body for covering a semiconductor element and the preferred range of the precipitation amount of Zn2SiO4 are the same as those of the glass for covering a semiconductor element.

[0044] In the sintered body for covering semiconductor elements of the present invention, the porosity is preferably 10% or less, 8% or less, and particularly preferably 5% or less. If the porosity is too high, the coverage becomes insufficient, which may have an adverse effect on the pressure resistance. In addition, in practice, the lower limit of the porosity is 0.1% or more.

[0045] Alternatively, a nucleating agent such as ZnO powder may be mixed with amorphous glass powder and then the mixed powder may be heat treated to produce a sintered body for covering a semiconductor element containing Zn2SiO4 as a main crystal.

[0046] Example

[0047] Hereinafter, the present invention will be described in detail based on examples. In addition, the following examples are only illustrative. The present invention is not limited in any way by the following examples.

[0048] Table 1 shows Examples (Samples No. 1 to No. 5) of the present invention and Comparative Examples (Samples No. 6 to No. 9).

[0049] [Table 1]

[0050]

[0051] Each sample was prepared as follows. First, the raw material powder was mixed to obtain a batch material having the glass composition shown in the table, and then melted at 1500°C for 1 hour to vitrify. Next, the molten glass was formed into a film, pulverized with a ball mill, and classified using a 350-mesh sieve to obtain an average particle size D. 50 The glass powder is 12 μm.

[0052] The volume ratio of Zn2SiO4, thermal expansion coefficient, surface charge density, defect inclusion condition, warpage amount and porosity of each sample were evaluated. The results are shown in Table 1.

[0053] The volume ratio of Zn2SiO4 is determined as follows. The glass powder is molded into a button shape, heat treated at 800-950°C for 10 minutes, and then crushed in a mortar. The diffraction peak is obtained using an X-ray diffraction device, and the background is removed. Then, for the peak belonging to Zn2SiO4, the integrated intensity of the peak from the crystal is divided by the integrated intensity of the peak from the glass, and then multiplied by 100.

[0054] The thermal expansion coefficient is a value measured in a temperature range of 30 to 300° C. using a push rod type thermal expansion coefficient measuring device using a sample heat treated at 800 to 950° C. for 10 minutes as a measurement sample.

[0055] The surface charge density is measured as follows. First, each sample is dispersed in an organic solvent, attached to the surface of a silicon substrate by electrophoresis to a certain film thickness, and then fired at a temperature that allows crystallization to form a covering layer. Next, an aluminum electrode is formed on the surface of the covering layer, and a CV meter is used to measure the capacitance change in the covering layer to calculate the surface charge density.

[0056] The defect inclusion status was measured as follows: The glass on the fired silicon substrate was observed with a stereomicroscope, and if bubbles with a diameter of 10 μm or more were not observed, it was evaluated as "0", and if bubbles with a diameter of 10 μm or more were observed, it was evaluated as "×".

[0057] The warping amount is measured as follows. First, the silicon substrate is placed on a platform in a downwardly convex manner, and any point on the circumference of the silicon substrate is fixed tightly to the platform with double-sided tape. Next, a laser displacement meter is used to measure the displacement of the height on a straight line passing through the fixed point of the silicon substrate and the center of the circle. The difference in height between the highest point and the lowest point of the obtained displacement is calculated, and the difference is evaluated as the warping amount. In addition, if the warping amount is less than 300μm, it can be said that the warping amount is small.

[0058] The porosity is measured as follows. First, glass powder and photoresist liquid are mixed and uniformly coated on a smooth silicon substrate of known weight. Next, it is fired at 500°C for 1 hour and at 950°C for 20 minutes. The thickness of the glass sintered film is then measured with a micrometer, and the weight is measured to obtain the volume density of the glass sintered film. Next, "(Glass density - sintered film volume density) / glass density" is calculated as the porosity.

[0059] As can be seen from Table 1, the thermal expansion coefficient, surface charge density and warpage of samples No. 1 to No. 5 show the expected values. In addition, the defect inclusion condition is also good. Therefore, it is considered that samples No. 1 to No. 5 are suitable as semiconductor element covering materials used in covering low-voltage semiconductor elements.

[0060] On the other hand, sample No. 6 had no crystals precipitated, had a high thermal expansion coefficient, and had poor evaluation of warpage. Samples No. 7 and No. 8 had strong crystallinity, and their viscosity increased rapidly during firing, thus containing defects. Sample No. 9 had too strong devitrification and could not be formed into glass.

Claims

1. A semiconductor element covering glass, characterized in that: The glass composition contains, by mol%, SiO2 30% to less than 53%, ZnO 15% to 30%, Al2O3 2% to 14%, B2O3 0 to 10%, MgO+CaO greater than 11% and less than 30%, and contains substantially no lead component.

2. The semiconductor element covering glass according to claim 1, wherein: After the heat treatment, the glass for covering a semiconductor element contains Zn2SiO4 as a main crystal.

3. A semiconductor element covering material, characterized in that: The semiconductor element covering material includes glass powder, and the glass powder contains the semiconductor element covering glass according to claim 1 or 2.

4. The semiconductor element covering material according to claim 3, characterized in that: After the heat treatment, the thermal expansion coefficient of the semiconductor element covering material in the temperature range of 30°C to 300°C is 20×10 -7 / ℃ and above 48×10 -7 / ℃ below.

5. A sintered body for covering a semiconductor element, characterized in that: The semiconductor element covering sintered body contains Zn2SiO4 as a main crystal, and the volume ratio of Zn2SiO4 is 10% to 40%.

6. A sintered body for covering a semiconductor element, characterized in that: The semiconductor element covering sintered body contains Zn2SiO4 as a main crystal and has a porosity of 10% or less.

7. The sintered body for covering a semiconductor element according to claim 5 or 6, characterized in that: The glass composition contains, by mol%, SiO2 30% to less than 53%, ZnO 15% to 30%, Al2O3 2% to 14%, B2O3 0 to 10%, MgO+CaO greater than 11% and less than 30%, and contains substantially no lead component.

Citation Information

Patent Citations

  • JP1973043275A

  • JP1975129181A

  • Semiconductor coating glass

    JP1989049653B2

  • Method for producing electronic component passivated by lead free glass

    JP2008162881A